2014
DOI: 10.1590/0004-2730000003390
|View full text |Cite
|
Sign up to set email alerts
|

Association of leptin levels with pathogenetic risk of coronary heart disease and stroke: a meta-analysis

Abstract: Objective: This meta-analysis aimed to investigate the association of leptin levels with pathogenetic risk of CHD and stroke. Materials and methods: Studies were identified in the PubMed, Embase, and Springer link database without language restriction. Odds ratios (ORs) and corresponding 95% confidence intervals (95% CIs) were used as effect indexes. The association of leptin levels with pathogenetic risk of CHD and stroke, as well as the risk variation of CHD with each additional one unit of leptin level were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 26 publications
1
22
0
5
Order By: Relevance
“…However, the association between high leptin concentration and risk of CVD is controversial. A published meta-analysis, comprising eight nested case-control studies with a total of 1980 CVD patients and 11567 participants, indicated a significant association between leptin and pathogenetic risk of CHD and stroke [21]. In contrast, the latest research studies did not find the same association [2224].…”
Section: Introductionmentioning
confidence: 99%
“…However, the association between high leptin concentration and risk of CVD is controversial. A published meta-analysis, comprising eight nested case-control studies with a total of 1980 CVD patients and 11567 participants, indicated a significant association between leptin and pathogenetic risk of CHD and stroke [21]. In contrast, the latest research studies did not find the same association [2224].…”
Section: Introductionmentioning
confidence: 99%
“…In hypertension, leptin induces endothelial nitric oxide synthase expression and vasodilation by the direct action of leptin on vascular endothelial cells [22]. However, the activation of sympathetic nerves increases blood pressure, and the net effect of leptin is the induction of arteriosclerosis [23, 24]. …”
Section: Introductionmentioning
confidence: 99%
“…For example, hyperleptinemia and hypoadiponectinemia have been associated with an increase in fat tissue [2,3] and prediabetes [4], respectively. Additionally, a meta-analysis [5] reported a significant association between leptin and the risk of cardiovascular diseases (CVD; OR 1.90, 95% CI 1.06-3.43) and strokes (OR 2.14, 95% CI 1.48-3.08). Conversely, low adiponectin levels have been associated with increased cardiovascular events and mortality rates [6].…”
Section: Introductionmentioning
confidence: 99%